PELAYANAN PUBLIK SEBAGAI ALTERNATIF VISI KEILMUAN - Pramono, Joko (Transformasi, 2011)
Abstract Public service become the cynosure over all paradigm of public administrative science. Two especial paradigm, that is clasical public administration and new public administration paradigm, placing public service in special position, besides public policy. This matter do not get out of the especial function of state before its people, that is service. Contemporary opinion [is] which bayak conversed by circle of administrative science expert given by the lebel sound governance center at governmental sector service, private sector, society and international community. That's a reason why public service can be made alternative of science vision program the study of public administrative science. Kata Kunci: Administrasi; Pelayanan; publik; dan Paradigma